PENERAPAN METODE LATIHAN SIAP UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS I SD NEGERI 006 TERPADU KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Lamra Hairani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this classroom action research (PTK) is the low ability of first-grade students at SD Negeri 006 Terpadu Kubang Jaya, Kecamatan Siak Hulu, in solving arithmetic operations. To address this learning problem, the Ready Exercise method was applied. The research problem is formulated as follows: Can the application of the Ready Exercise method improve the mathematics learning outcomes of first-grade students at SD Negeri 006 Terpadu Kubang Jaya, Kecamatan Siak Hulu? The purpose of this research is to enhance the learning outcomes of first-grade students in mathematics by applying the Ready Exercise method. The results of this action research indicate that the implementation of the Ready Exercise method effectively improves learning outcomes. The average score increased from 42.25 (categorized as fairly good) before the action, to 62.50 (good) in the first cycle, and further to 81.50 (very good) in the second cycle. Before the intervention, only 13 students (32.5%) achieved completeness in learning outcomes. This number increased to 22 students (55%) in the first cycle and reached 37 students (92.5%) in the second cycle. Based on observations, the researcher noted that first-grade students at SD Negeri 006 Terpadu Kubang Jaya understood the Ready Exercise method and were able to work collaboratively in learning activities. The use of the Ready Exercise method successfully addressed the low mathematics learning outcomes, achieving significant improvement by the second cycle.